Effects of different feed types and light intensity levels on the growth and reproduction of clam shrimp, Cyclestheria hislopi (Baird, 1859) - Iing, Xiao Wei (2012)
Clam shrimp (a Phyllopod order conchostraca) is a freshwater crustacean belonging to the subclass of Branchiopoda. It possesses a bivalve carapace, inhabit mainly the benthos but can swim freely in water column. Cyclestheria hislopi is the only species that has been reported to be found in permanent water body. The objective of this study was to determine the effects of different types of feed and different levels of light intensity on the growth and reproduction of Cyclestheria hislopi. Three types of feed (artificial fined powdered diet, microalgae Scenedesmus sp. and microalgae Chlorella sp.) were used for the feeding experiment. Five levels of light intensity (0, 15, 30, 45, and 60 μmol m-2 s-1) were used for the light intensity experiment. Cyclestheria hislopi showed the best growth and reproduction when fed with Chlorella sp. and when were kept under the lowest light intensity. This study illustrated that Cyclestheria hislopi prefered small sized microalgae as its food and tend to live in subdued light condition. It is important to understand the optimum condition for clam shrimp to grow and reproduce so that culturing of this species for use in aquaculture can be successful.